AN ANALYSIS OF SUNDANESSE TEXTBOOK IN UNPAD.AC.ID: A CRITICAL DISCOURSE ANALYSIS - Humaira Restu Maulidia; Cita Mustika Kusumah; Dien Novita (English Journal Literacy Utama, 2023)
The current study investigates the representation of UNPAD, which raises the issue of Sundanese textbooks on the UNPAD website. It focuses on how the article entitled "Sundanese Textbooks Still Lacking Attention to Speech Language Level" on the UNPAD website represents the current Sundanese textbooks that are used by the students in the school. The data is taken from the article on UNPAD's website, www.unpad.ac.id. This study used a qualitative research design with the characteristics of a descriptive study. In qualitative research, a single phenomenon of interest is researched before being stated in a purpose statement. The study's findings indicate that the use of Sundanese textbooks is viewed negatively due to a lack of attention to the language's level